Review of the Fund's Strategy on Overdue Financial Obligations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Reviews progress under the Fund's strengthened cooperative strategy on overdue financial obligations and proposes to extend the availability of the rights approach, which expires on August 31, 2005, by another year. The rights approach remains a potentially important element of the intensified collaborative approach for arrears clearance for the three members that remain eligible, Liberia, Somalia, and Sudan.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Sudan